Über eine fehlgedeutete äthiopische Art der Gattung Dichaetomyia Malloch. (Diptera: Muscidae). - Pont, Adrian C. (Contributions to Entomology = Beiträge zur Entomologie, 1966)
The species Spilogaster analis Stein has not been recorded since its original description, nor was it correctly recognised in the most recent revisionary work on Ethiopian Dichaetomyiini (Van Emden, 1942). The author designates a lectotype, redescribes the species, and places it correctly in Van Emden’s key. Nomenclatural Acts analis (Stein, 1906) (Dichaetomyia (Panaga)), Lectotype; comb. n. hitherto Spilogaster analis